Rising of the Phoenix: Mitigating Political Risk through Knowledge Management—Behn, Meyer & Co., 1840–1959 - Yacob, Shakila (Cambridge University Press, 2018)
This article examines how a German firm in the Malay Peninsula - Behn, Meyer & Co. - capitalized on its knowledge management to overcome political risks during the period from 1840 until 1959. During the two world wars, all assets and properties of the Behn Meyer firm were systematically expropriated because of the introduction of the Alien Enemies (Winding Up) Act of 1914 and the subsequent imposition of a ten-year ban by the British colonial administration in the Malay Peninsula. However, Behn Meyer's resilience and flexible outlook, as demonstrated by its management of political risks during these tumultuous periods, enabled it to rebuild its business interests and reestablish a foothold in postcolonial Malaysia and the region. This article argues that Behn Meyer displayed an exemplary business strategy, utilized its understanding of the geopolitics of the area, and leveraged its local and international networks to ensure its survival and longevity in the most tumultuous period in the history of the world.